Under voltage load shedding using voltage stability indices - Hamid M.H.A.; Hashim H.; Rashid H.A.A.; Abidin I.Z. (IEEE Computer Society, 2023)
Voltage instability is characterized by loss of a stable operating point due to reactive power deficiency, which causes a drop of voltage profile in significant part of the system. The voltage is stable if the system can maintain its voltage within the acceptable limits when there is a change in load admittance. Voltage collapse may occur when the system is subjected to system fault(s); the occurrence of this phenomenon can be either slowly or drastically depending on the severity of the fault(s) [1]. Therefore, it is more accurate to analyze the system behavior dynamically with respect to voltage stability. This paper presents under voltage load shedding scheme using voltage stability indexes based on system behavior in dynamic environment. © 2014 IEEE.